Greener homes: An ex-post estimate of the cost of carbon dioxide emission reduction using administrative micro-data from the republic of Ireland - Eimear Leahy; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2011)
We assess the subsidy for the installation of biomass boilers and wood gasification boilers under the Greener Homes Scheme in Ireland. We find that the (implicit) subsidy per tonne of carbon dioxide avoided varies hugely across households. The current policy costs 17% too much for the emissions avoided, or avoids 17% too few emissions for the money spent. The subsidy reduces welfare (including environmental benefits) by 42%.
Keywords: 330; climate policy; Ireland; ex-post evaluation